(untitled) (African Journal of Biomedical Research, 2021)
Meal skipping is a documented unhealthy practice associated with obesity, poor dietary choices and development of chronic diseases. Undergraduate students are predisposed to skipping meals for several reasons. This study therefore determined the prevalence of meal skipping among students in Sagamu. Southwest Nigeria. A cross-sectional study was conducted among 350 undergraduate students of the College of Health Sciences, Olabisi Onabanjo University, Sagamu, Nigeria, selected via multi-stage sampling. Data were collected using a semi-structured, self-administered questionnaire, stadiometre and analyzed with SPSS 20.0. Relevant descriptive and inferential statistics were calculated, with level of significance (p) set at <0.05. Participation was fully voluntary. The mean age of respondents was 23.4 ±2.3 years. The proportion of students who skipped meals was 92%; breakfast was most frequently skipped (82.6%). Reasons for skipping meals included: busy schedules (82.3%); food rationing (16.3%); inability to cook (10%). Meal skipping was associated with poor concentration at school, mood swings, irritable behavior, reduced comprehension (p<0.05). Most (69.1%) respondents had a normal body mass index; only 6.9% of respondents were obese. Meal skipping was highly prevalent among undergraduate students in Sagamu. Adequate nutrition education on healthy eating and health promotion activities are necessary to reduce the prevalence of this unhealthy practice.